1 Coronary microvascular dysfunction in stable coronary artery disease: the CE-MARC 2 coronary physiology sub-study. (25th January 2018) - Corcoran, David S; Young, Robin; Adlam, David; McConnachie, Alex; Mangion, Kenneth; Ripley, David; Cairns, David; Brown, Julia; Bucciarelli-Ducci, Chiara; Kharbanda, Rajesh; Oldroyd, Keith G; McCann, Gerry P; et al.
Abstract : Background: In patients with angina undergoing invasive diagnostic management, no obstructive coronary artery disease (CAD) is a common finding. Coronary microvascular dysfunction may be relevant. We aimed to assess the prevalence of abnormal coronary microvascular function in patients with suspected CAD. Methods: CE-MARC 2 was a prospective multicentre randomised trial of functional imaging vs guideline-based management in patients with suspected CAD. Invasive angiography was protocol-directed based on the presence of inducible ischaemia on non-invasive stress testing, or directly as per NICE guideline care. Fractional flow reserve (FFR) and microvascular function (coronary flow reserve (CFR), index of microcirculatory resistance (IMR), resistance reserve ratio (RRR)) were measured in major epicardial vessels with stenosis ≥40-≤90%. Results: 267/1202 (22.2%) patients underwent angiography and 81 (30%) patients had FFR measured. 63 (78%) of these patients had microvascular function assessed in 85 arteries (age 58.5±8.2 years; 47 (75%) male). 25/63 (40%) patients had no obstructive CAD, and of these 17 (68%) had an abnormality in at least one parameter of microvascular function (figure). Conclusions: Coronary microvascular dysfunction is common in patients with angina and no obstructive CAD. Invasive microvascular function assessment may be relevant for clinical decision-making.